(untitled) (Research, Society and Development, 2023)
The research addresses the importance of adequate nutrition during pregnancy for the health of the mother and the healthy development of the baby. The maternal diet influences the child’s weight in childhood and the risk of obesity, as well as the prevention of nutritional risks to the mother and fetal development. Adequate nutrition during pregnancy guarantees positive results, biological reserves for childbirth, adequate lactation and correct weight gain, avoiding complications such as diabetes and gestational hypertension. Inadequate nutrition during pregnancy results from mothers’ lack of knowledge about its importance, affecting fetal development and the health of the newborn. The study highlights the need for knowledge about a healthy diet during this period, avoiding health problems for the mother that impact the baby. The aim is to highlight the adversities of inadequate nutrition during pregnancy and its effects on healthy fetal development. This exploratory study based on narrative review collects data from secondary sources such as Google Scholar, SciElo, Lilacs and PubMed, using descriptors such as pregnancy, nutrition and fetal development. This project’s main objective is to highlight the importance of pregnant women knowing about adequate nutrition for the healthy development of their baby. In the analysis, relevant works were selected with inclusion and exclusion criteria. Awareness about nutrition during pregnancy is vital, and this project seeks to educate pregnant women about healthy nutritional choices, aiming for a healthier future for mother and child. Nutritional education during pregnancy is crucial, playing a fundamental role in promoting maternal well-being.